Interactive systems in the Prophetic Hadith from a pragmatic perspective - Nemissi, Amel (El Omda in Linguistics and Discourse Analysis, 2024)
(not more than 10 Lines) Article info The Noble Prophetic hadith has always been a means of Islamic advocacy, and therefore it is not surprising that we return to society to provide us with explanations for artistic phenomena, especially the art of advocacy discourse that relies on language as a tool of expression. ; Because the progress in the analysis of discourse did not have a share in the prophetic discourse, so it remained confined to the ideological studies that had accumulated throughout history, and were represented in simple and ordinary explanations that dispersed here and there between the books of jurisprudence and history. This research came as an attempt to reveal the characteristics of the prophetic discourse in its relation to the influence, directive and persuasive systems through the deliberative approach based on addressing the semantics of the discourse, and monitoring the movement of linguistic evidence in connection with the conditions of use, and the reception contexts that surround this discourse